Apr 24 08:00 AM PDT  09:00 AM PDT Join the Live Chat April 24th at 8 am PT. Learn the best strategies for acing the Verbal section. From Sentence Correction tactics to 3 keys for solving Reading Comprehension questions and tips for Critical Reasoning questions. Apr 24 08:00 PM EDT  09:00 PM EDT Maximize Your Potential: 5 Steps to Getting Your Dream MBA Part 3 of 5: Key TestTaking Strategies for GMAT. Wednesday, April 24th at 8 pm ET Apr 25 10:00 PM PDT  11:00 PM PDT Join an exclusive workshop for GMAT Club members and learn how to cut your preparation time by 50% and still reach a 700+ on the GMAT. Limited for the first 99 registrants. Register today! Apr 27 07:00 AM PDT  09:00 AM PDT Attend this webinar and master GMAT SC in 10 days by learning how meaning and logic can help you tackle 700+ level SC questions with ease. Apr 28 07:00 AM PDT  09:00 AM PDT Attend this webinar to learn a structured approach to solve 700+ Number Properties question in less than 2 minutes. Apr 29 08:00 AM PDT  09:00 AM PDT Join a free live webinar and learn timemanagement tactics that will guarantee you answer all questions, in all sections, on time. Save your spot today! May 01 10:00 PM PDT  11:00 PM PDT Target Test Prep is kicking off spring with a fresh giveaway contest! For a limited time, you have a chance to win 4 months of full, FREE access to our 5star rated GMAT Quant course.
Author 
Message 
TAGS:

Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 54496

If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
15 Jun 2017, 07:33
Question Stats:
90% (00:48) correct 10% (00:59) wrong based on 318 sessions
HideShow timer Statistics
If \(−x − 2 = −−(6 − 2)\), then x = (A) –5 (B) –2 (C) 0 (D) 2 (E) 5
Official Answer and Stats are available only to registered users. Register/ Login.
_________________



Director
Joined: 04 Dec 2015
Posts: 750
Location: India
Concentration: Technology, Strategy
WE: Information Technology (Consulting)

If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
15 Jun 2017, 07:42
Bunuel wrote: If \(−x − 2 = −−(6 − 2)\), then x =
(A) –5 (B) –2 (C) 0 (D) 2 (E) 5 \(−x − 2 = −−(6 − 2)\) \(x  2 = −−4\) \((4) = x 2\) \(x = 42 = 2\) . Answer D...



CEO
Joined: 12 Sep 2015
Posts: 3589
Location: Canada

Re: If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
15 Jun 2017, 08:29
Bunuel wrote: If \(−x − 2 = −−(6 − 2)\), then x =
(A) –5 (B) –2 (C) 0 (D) 2 (E) 5 Given: −x − 2 = −−(6 − 2) Simplify right side: −x − 2 = −−(4) Evaluate right side: −x − 2 = −(4) Simplify right side: −x − 2 = −4 Add 2 to both sides: −x = 2 Multiply both sides by 1 to get: x = 2 Answer: Cheers, Brent
_________________
Test confidently with gmatprepnow.com



Senior SC Moderator
Joined: 22 May 2016
Posts: 2652

If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
15 Jun 2017, 09:09
GMATPrepNow wrote: Bunuel wrote: If \(−x − 2 = −−(6 − 2)\), then x =
(A) –5 (B) –2 (C) 0 (D) 2 (E) 5 Given: −x − 2 = −−(6 − 2) Simplify right side: −x − 2 = −−(4) Evaluate right side: −x − 2 = −(4) Simplify right side: −x − 2 = −4 Add 2 to both sides: −x = 2 Multiply both sides by 1 to get: x = 2 Answer: Cheers, Brent GMATPrepNow , Brent, I have a feeling this is a really dumb question, but I am confused. I considered two cases, the one you showed, and (4) =  (x  2) (4) = x + 2  6 = x Upon plugging in (x = 6) into original equation, it did not satisfy (LHS became +4, not negative value as needed). So I plugged in x = 2, and it worked. Question: when do you know that you do not need to consider both cases? I thought about whether or not I'd be able to "see," immediately, that the alternative case would not yield a negative LHS. Not likely. Maybe this kind of equation never requires more than one case? What am I missing?
_________________
Listen, are you breathing just a little, and calling it a life?  Mary Oliver
For practice SC questions with official explanations that were posted and moderated by the SC Team, go to SC Butler here: https://gmatclub.com/forum/projectscbutlerget2scquestionseveryday281043.html



CEO
Joined: 12 Sep 2015
Posts: 3589
Location: Canada

Re: If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
15 Jun 2017, 12:24
genxer123 wrote: Brent, I have a feeling this is a really dumb question, but I am confused.
I considered two cases, the one you showed, and (4) =  (x  2) (4) = x + 2  6 = x
Upon plugging in (x = 6) into original equation, it did not satisfy (LHS became +4, not negative value as needed). So I plugged in x = 2, and it worked.
Question: when do you know that you do not need to consider both cases? I thought about whether or not I'd be able to "see," immediately, that the alternative case would not yield a negative LHS. Not likely.
Maybe this kind of equation never requires more than one case? What am I missing? We need to consider two cases when there are variables inside the absolute value symbols. For example, if we have x  2 = 6, then we must consider two cases: case a: x  2 = 6 case b: x  2 = 6 If there are no variables inside the absolute value symbols, then we need not consider two cases. For example, in the equation x = 3, we can conclude that x = 3 Conversely, in the equation x = 3, we can conclude that x = 3 or x = 3 Cheers, Brent
_________________
Test confidently with gmatprepnow.com



Current Student
Joined: 12 Oct 2015
Posts: 217
Location: Canada
Concentration: Leadership, Accounting
GPA: 3
WE: Accounting (Accounting)

Re: If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
19 Jun 2017, 11:36
This is an amazing question. Adding to my list of must do questions to redo.
_________________



Retired Moderator
Joined: 19 Mar 2014
Posts: 931
Location: India
Concentration: Finance, Entrepreneurship
GPA: 3.5

Re: If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
24 Jun 2017, 15:40
\(−x − 2 = −−(6 − 2)\) \(x  2 = (4)\) \(x  2 =  4 \) \(x  2 = 4\) \( x =  2\) \(x = 2\) Hence, Answer is D
_________________
"Nothing in this world can take the place of persistence. Talent will not: nothing is more common than unsuccessful men with talent. Genius will not; unrewarded genius is almost a proverb. Education will not: the world is full of educated derelicts. Persistence and determination alone are omnipotent."
Best AWA Template: https://gmatclub.com/forum/howtoget60awamyguide64327.html#p470475



Target Test Prep Representative
Status: Head GMAT Instructor
Affiliations: Target Test Prep
Joined: 04 Mar 2011
Posts: 2825

Re: If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
06 Jul 2017, 17:28
Bunuel wrote: If \(−x − 2 = −−(6 − 2)\), then x =
(A) –5 (B) –2 (C) 0 (D) 2 (E) 5 We can simplify the equation: x  2 = (6  2) x  2 = (4) x  2 = 4 x = 2 x = 2 Answer: D
_________________
5star rated online GMAT quant self study course See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews



Intern
Joined: 06 Feb 2017
Posts: 7

Re: If −x − 2 = −−(6 − 2), then x =
[#permalink]
Show Tags
13 Jul 2017, 08:48
Correct option:D Time take: 0:56 sec Solution x2=(62) x2=4 x2=4 x=2 Dividing both sides by minus x=2




Re: If −x − 2 = −−(6 − 2), then x =
[#permalink]
13 Jul 2017, 08:48






